Evaluation of Lead Presence in Lipstick Sample using Atomic Absorption Spectroscopy: A Forensic Study - Gaurav Kumar Singh (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background- The increasing prevalence of daily cosmetic product usage has given rise to new health concerns. A wide range of cosmetic products, from affordable to high-end, are available on the market. These products can have a significant impact on human skin, mucous membranes, hair, and nails, sometimes leading to allergies and other related issues. This may be attributed to the presence of toxic chemical components in the majority of cosmetics used daily. Material and Methods – The quantity of lead in the lipsticks was determined using atomic absorption spectroscopy. For this research, locally manufactured and widely used lipsticks were chosen. Results – The outcomes of this research are distressing, necessitating the promotion of knowledge about the application of lipsticks among the LGBTQIA+ community, which comprises Gay, Lesbian, Bisexual, Transgender, Queer, Intersex, and Asexual individuals. This study analyzed samples with Pb concentrations ranging from 1.85 mg/L to 2.25 mg/L. Conclusion – Identifying lead in cosmetic products cannot be emphasized enough, given its detrimental effects on human health. Atomic absorption spectroscopy (AAS) is an exceedingly sensitive and precise method for detecting lead in these products. Our studies recommend that it is essential to establish a standard testing program to screen for lead and other harmful metals in cosmetics, particularly lipsticks, in numerous cosmetic laboratories.